Ultra-thin high-efficiency mid-infrared transmissive Huygens meta-optics - Li Zhang (Nature Portfolio, 2018)
Mid-IR optics can require exotic materials or complicated processing, which can result in high cost and inferior quality. Here the authors report the demonstration of high-efficiency mid-IR transmissive lenses based on dielectric Huygens metasurface, showing diffraction limited focusing and imaging performance.